Hematopoietic cell transplantation activity of Turkey in 2014: Ongoing increase in HCT rates. Issue 1 (February 2016) - Tekgündüz, Emre; Şencan, İrfan; Kapuağası, Arif; Ünal, Doğan; Öztürk, Murat; Gümüş, Eyüp; Göker, Hakan; Tavil, Emine Betül; Ertem, Mehmet; Çetin, Mustafa; Arat, Mutlu; Soysal, Teoman; et al.
Abstract: Hematopoietic cell transplantation is an established treatment option with curative potential for a variety of clinical conditions. The last decade especially witnessed a remarkable increase in HCT activity in Turkey. In 2014, 696 pediatric and 2631 adult (total 3327) HCT were performed in Turkey. Corresponding transplant rates per 10 million inhabitants for autologous-HCT and allogeneic-HCT were 226 and 202, respectively. Total HCT procedures in Turkey increased 177% in the last 5 years and 791% in the last 14 years. This report focuses mainly on HCT activity of Turkey in 2014 based on the national HCT registry and presents a general picture of national HCT activity.